Промислові випробування нових техніко-технологічних засобів будівництва горизонтальних та похило – спрямованих свердловин - Кунцяк, Я.В.; Мартинюк, Д.М.; Булатов, К.В.; Новіков, В.Д.; Кунцяк, Р.Я. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
The new technical and technological means for a decrease of the cost at horizontal and controlled directional drilling are offered. The authors suggest an application method the PDC bits with low energy of rock destruction and controlled systems. The use results of technical-technological complex are described at 155 and 23 wells (Kachanivka field, JSC “Ukrnafta”).